Infant airway microbiota and topical immune perturbations in the origins of childhood asthma - Jonathan Thorsen (Nature Portfolio, 2019)
Here, Thorsen et al. examine the microbiota during the first three months of life in a cohort of 700 children and find that microbial diversity and the relative abundances of Veillonella and Prevotella in the airways at one month of age are associated with topical immune mediators and asthma by age 6 years.